Addressing Implementation Challenges of Minimum Service Standards in Local Government Using Soft System Methodology: A Case Study of Bekasi City, Indonesia - Maharina Desimaria; Amy Yayuk Sri Rahayu; Junarti Junarti; Reni Novia (Nyimak: Journal of Communication)
Minimum Service Standards (MSS) are specific provisions that must be fulfilled by local governments as a concurrent obligation targeted to reach 100% every year. However, as of 2023, Bekasi City has not achieved the set targets. The MSS Service Quality Achievement Index in Bekasi City is still relatively low, with all 6 MSS falling under the "Unfinished" category. This indicates problems in MSS implementation, including issues related to policy, planning, budgeting, and execution involving policymakers, implementers, and service recipients. This study aims to map the challenges in implementing MSS in Bekasi using Soft System Methodology (SSM) analysis and provide recommendations for addressing the identified issues. This research adopts a qualitative approach with action research methodology. Data collection techniques include analyzing relevant documents to understand the problem situation and conducting SSM's seven stages of analysis. This study contributes to the literature by applying SSM to understand and enhance policy implementation at the local level, which can be adapted to similar contexts in neighboring Malaysia and Singapore. The findings serve as a reference for improving MSS implementation and enhancing public service quality.